Community Education Through the ABCD Method to Improve Knowledge About the Importance of Breakfast at SD Negeri 104226 Sukarende - Ritonga, Futri; Berutu, Mastuti; Tanjung, Vindy Ammadhea; Kinanti, Widya; Matondang, Nizar Zulmi; Siregar, Putra Apriadi (PROMOTOR, 2025)
Breakfast is the best way to give the brain the energy it needs to focus in class. Breakfast is very important to meet nutritional needs in the morning, especially for children who have many academic obligations. The aim of this research is to determine the effect of counseling about the importance of breakfast on knowledge and attitudes at SD Negeri 104226 Sukarende. In this research, it was carried out using the ABCD method. The outreach media used in this research is PPT material and showing animated videos about the importance of breakfast. The research results showed that during the counseling, teachers, parents and children all responded quite well. Breakfast has a very important role in supporting the health and learning achievement of school children. Breakfast has two purposes, namely providing adequate nutrition and maintaining the body's immune system, thus allowing the body to carry out its tasks efficiently. Children need energy for physical activity, studying in class, and participating in various other school activities. Without breakfast, the body will take energy reserves from stored glycogen, but this will soon run out and cause students to feel tired quickly, lack energy, and can even faint. Media-based counseling for elementary school students is very useful and more effective because media-based counseling can increase knowledge and understanding and is more easily absorbed by students at SD Negeri 104226 Sukarende. For students at SD Negeri 104226 Sukarende, breakfast is very important to start daily activities and study well.